The impact on Anti-Mullerian Hormone (AMH), uterine fibroid size and uterine artery patency following Uterine Fibroid Embolization (UFE) with a resorbable embolic agent. (20th October 2022) - Hacking, Nigel; Vigneswaran, Ganesh; Maclean, Drew; Bryant, Timothy; Umranikar, Sameer; Cheong, Ying; Modi, Sachin
Abstract: The effect of Uterine Fibroid Embolization on fertility and ovarian reserve remains uncertain. We assessed the impact of a new resorbable, spherical particle (Gelbead) on concentration of Anti-Mullerian (AMH) hormone, fibroid volume and uterine artery patency. This prospective cohort study recruited consecutive patients from July 2017 to June 2018. Serum AMH, fibroid and uterine volume, UFS-QOL (uterine fibroid score-quality of life) scores were measured prior to and at 1 month and/or 3 months post embolization. Twenty-four participants were enrolled (median age 44 years, uterine volume 484 cm 3, initial dominant fibroid volume 167 cm 3 ). One patient was lost to follow-up. AMH (median ± SD) immediately prior to embolization was 3.2 ± 13.7 pmol/L. At 1-month postembolization, AMH was 4.1 ± 8.6 pmol/L and at 3 months 4.4 ± 8.6 pmol/L. We found no significant difference in AMH levels between baseline and at 1 month ( p = 0.58) or baseline and 3 months ( p = 0.17). The median dominant uterine fibroid volume decreased (167 to 64 cm 3, p < 0.001). At 3 months post-embolization, 17/23 patients had patent uterine arteries bilaterally (73.9%). UFE with Gel-bead did not significantly affect AMH at 3 months post embolization, whilst maintaining a high rate of uterine artery patency.